2009
DOI: 10.1902/jop.2009.080637
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Acetaminophen–Caffeine Compared to Ibuprofen in the Control of Postoperative Pain After Periodontal Surgery: A Crossover Pilot Study

Abstract: Acetaminophen, 500 mg, with caffeine, 30 mg, can be used efficiently in controlling postoperative pain after open flap debridement, especially in patients with gastric ulcers or bleeding tendency because acetaminophen is less hazardous than ibuprofen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 38 publications
0
31
0
2
Order By: Relevance
“…Many studies have investigated the effect of different NSAIDs to control postoperative pain after open‐flap surgery with generally favorable results . However, to the author's knowledge there was no available study on the use of topical NSAIDs at donor site wound model after periodontal plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the effect of different NSAIDs to control postoperative pain after open‐flap surgery with generally favorable results . However, to the author's knowledge there was no available study on the use of topical NSAIDs at donor site wound model after periodontal plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, caffeine can increase gastrointestinal movements and increase absorption of other analgesics. Therefore, presence of caffeine along with other analgesics is recommended to increase their efficacy (13). Mehrvarz et al compared the analgesic effects of naproxen, Novafen and tramadol in preventing pain after radicular surgeries with those of a placebo and reported that all the three medications were effective (14).…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental pain model, paracetamol (1,000 mg) when combined with caffeine (130 mg) had a sustained antinociception‐enhancing effect [30]. Moreover, the combination of paracetamol and caffeine has been shown to be as efficacious as ibuprofen after periodontal surgery [31] and naproxen sodium in tension‐type headache [32]. However, few studies have evaluated the efficacy of a caffeine‐analgesic combination vs the same analgesic alone.…”
Section: Introductionmentioning
confidence: 99%